Increasing soak time improves size selection and harvesting patterns in common whelk (Buccinum undatum) pot fisheries - Moritz Eichert; Bent Herrmann; Michel J. Kaiser; Jure Brčić (Reviews in Fish Biology and Fisheries, 2026)
Common whelk is a neo-gastropod that is intensively fished on the west and east temperate Atlantic with baited pots. The UK hosts the largest Whelk fishery contributing 10–15% to the national Shellfish landings, worth 15–27 million £ a year. The fishery is regulated by a minimum conservation reference size (MCRS) which for most areas is set at 45 mm total shell length. However, scientific information quantifying the size selectivity for pots to catch common whelk and to what extent soak time applied affects it is limited leaving it unknown to what extent the existing fishing practice obtains a size selection that matches the MCRS. Therefore, experimental fishing trials were conducted to fill this knowledge gap. The results obtained demonstrated that soak time significantly affected the size selectivity for the pots. Specifically, it was found that only 75% of the whelks would be size sorted if soaking time for the pots was as short as 18h while with an extended soaking time to 46h practically all (97%) whelks entering were size selected by the escape gaps in the pots. Therefore, soaking time needs to be considered to obtain an efficient size selection at the seabed.

Low injury rates on snow crab (Chionoecetes opilio) overrun by demersal trawls - Jesse Brinkhof; Ilmar Brinkhof; Manu Sistiaga; Bent Herrmann; Helene S. Jensen (Reviews in Fish Biology and Fisheries, 2026)

Hook modification to reduce rockfish and Pacific spiny dogfish bycatch in the U.S. West Coast Pacific halibut longline fishery - Dylan S. Heppell; Mark J. M. Lomeli; W. Waldo Wakefield; Bent Herrmann; Claude L. Dykstra; Ian J. Stewart (Reviews in Fish Biology and Fisheries, 2026)

Evaluating overall size selection pattern and seasonal variations for the commercially valuable cephalopod Loligo vulgaris in the Mediterranean bottom trawl fishery - Alexia Della; Chryssi Mytilineou; Bent Herrmann; Danai Mantopoulou-Palouka; Evgenia Lefkaditou; Antonello Sala; Christos Maravelias (Ocean & Coastal Management, 2026)

Effect of ground gear type on catch efficiency of demersal trawls - Ilmar Brinkhof; Bent Herrmann; Manu Sistiaga; Jesse Brinkhof (Regional Studies in Marine Science, 2026)

Size selectivity of hand dredges targeting black clam (Villorita cyprinoides) - V.R. Madhu; Bent Herrmann; Jure Brčić; Megha Madhav; K.K. Mohammed Jabir (Regional Studies in Marine Science, 2026)

Guidelines to Make Swimming Crab ( Portunus trituberculatus ) Pot Fishery Size Selective - Mengjie Yu; Bent Herrmann; Jure Brčić; Manu Sistiaga; Yixin Yang; Hui Liang; Liyou Zhang; Yanli Tang (Fisheries Management and Ecology, 2026)
Pot fisheries are a crucial component of small‐scale fisheries worldwide, characterized by their low environmental impact, high species selectivity, and superior catch quality. However, these fisheries are often constrained by poor size selectivity, which results in substantial bycatch of juvenile target species and remains a major challenge for pot fisheries management globally. Incorporating escape gaps or increasing mesh size are effective technical measures to improve pot size selectivity and reduce the unintended capture of undersized individuals. However, the implementation of these measures typically depends on traditional experimental sea trials, which are costly, time‐consuming, and restrict the number of gear designs that can be tested. This study focuses on the Chinese swimming crab ( Portunus trituberculatus ) pot fishery, which is the most economically important crab fishery along the Chinese coast. Laboratory experiments were conducted to establish predictive models for the size selectivity potential of swimming crab in pots. The size selectivity potential of a wide range of escape gap shapes and sizes, as well as mesh size and mesh opening angle, were investigated. The predictive models for the size selectivity potential were compared to earlier sea trial results and demonstrated their usefulness to predict swimming crab size selectivity. Based on these models, we provide guidelines to make swimming crab pot fishery size selective, which would contribute to the sustainable management of this pot fishery.

Size Selectivity and Exploitation Pattern of Traps for Japanese Mantis Shrimp (Oratosquilla oratoria) in the Bohai Sea - Qingchang Xu; Wenqiang Huang; Zhiwei Pang; Bent Herrmann; Zhaohai Cheng; Jiancheng Zhu; Xiansen Li (Fishes, 2026)
The Japanese mantis shrimp (Oratosquilla oratoria) is a commercially important crustacean species distributed around the coastal waters of China, which is harvested with both active and passive fishing gears. Among these, traps are one of the primary passive gears used in the Bohai Sea, which is one of the most important fishing grounds for Japanese mantis shrimp in northern China. However, the use of traps with a small mesh size challenges the sustainability of this fishery. Therefore, this study quantified the size selectivity and harvesting pattern for traps with different mesh sizes for harvesting Japanese mantis shrimp in the Bohai Sea. Results showed that the 50% retention length increased from 6.39 cm to 12.44 cm as mesh sizes increased from 20 (T20) to 60 mm (T60). T20 retained 86.8% and 100% of individuals, respectively, below (np-) and above (np+) the minimum landing size. Increasing mesh sizes decreased both np- and np+. Compared with T20, T30 reduced undersized catch by 67.8% while decreasing legal-sized catch by 8.2%. Increasing mesh sizes beyond T40 provided no significant reduction in np- but caused further reduction in np+. Therefore, the T30 mesh trap was recommended to replace the currently applied T20 in the Bohai Sea.

Addressing rigid gear rules under changing stock dynamics: A first empirical step towards flexible gear choice - Sissel Kolls Bertelsen; Jordan P. Feekings; Bent Herrmann; Marie Storr-Paulsen (Regional Studies in Marine Science, 2026)

Size limits for the use of Ballan wrasse (Labrus bergylta) as cleaner fish in salmon aquaculture cages - Terje Jørgensen; Manu Sistiaga; Bent Herrmann (Aquaculture, 2026)

Make fisheries better by reducing size selectivity in the North-east Arctic bottom trawl fishery - Ilmar Brinkhof; Manu Sistiaga; Bent Herrmann; Neil Anders; Jesse Brinkhof (Regional Studies in Marine Science, 2026)

Rebuttal to the response by Millar and Broadhurst - Bent Herrmann; Juan Santos; Manu Sistiaga; Jure Brčić; Junita D. Karlsen; Valentina Melli; Antonello Sala; Tiago Veiga-Malta; Jesse Brinkhof; Andrea Petetta; Mengjie Yu; Mark J.M. Lomeli; et al. (Fisheries Research, 2026)

The Effect of Mesh Size and Shape on Size Selectivity of White Croaker (Pennahia argentata) in Diamond-Mesh Codends for Demersal Trawl Fisheries - Bingzhong Yang; Bent Herrmann (Fishes, 2025)
White croaker (Pennahia argentata) is an ecologically and economically relevant fish species targeted by demersal trawls using diamond-mesh codends at fishing grounds in China, Japan, and Korea. However, the stock has been overexploited, and the capture of undersized individuals is of concern. Further, diamond-mesh codends are known to have varying mesh shape due to the fact that the opening angle in them varies along the codend and during the fishing process. Therefore, to fully understand the effect of mesh size and opening angle on the size selectivity of white croaker, experimental fishing trials and fall-through trials were conducted. By combining the results from these trials, a model was constructed to predict the effect of mesh size and mesh opening angle on size selectivity of white croaker. The predicted size selectivity results for white croaker fitted well with those from the sea trial experiments, which enabled us to use the model established to predict the size selectivity of diamond-mesh codends with a mesh size ranging from 15 to 90 mm and the effect on the exploitation pattern of the species in the fishery by changing the codend mesh size.

Size selecting for flatfish while avoiding cod - Zita Bak-Georgsen; Bent Herrmann; Juan Santos; Valentina Melli; Jordan P. Feekings; Daniel Stepputtis (Regional Studies in Marine Science, 2025)

Effect of codend mesh size on size selectivity and catch efficiency of common sole (Solea solea) - Ludvig Ahm Krag; Bent Herrmann; Rikke Petri Frandsen (Regional Studies in Marine Science, 2025)

Caught on camera: quantifying fish behaviour in relation to sorting grids - Nadine Jacques; Bent Herrmann; Manu Sistiaga; Jesse Brinkhof; Juan Santos; Ilmar Brinkhof (Reviews in Fish Biology and Fisheries, 2025)
This study analyses the behaviour of cod ( Gadus morhua ), haddock ( Melanogrammus aeglefinus ), saithe ( Pollachius virens ) and redfish ( Sebastes spp.) in relation to size-sorting grids from video recordings obtained during trawling in the Barents Sea. It quantifies how fish contact the grid, how frequently they do so, their escape success rate and whether they squeeze themselves through the grid bar spacings during the escape process. Fish primarily escaped by passing through the grid bars head-first or by contacting the grid with their dorsal side first. However, combined, these modes only occurred in 30%, 36%, 23% and 33% of all grid contact events for cod, haddock, saithe and redfish, respectively. Overall, approximately 35% of grid contact events of all sizes of cod, haddock and redfish and 14% of grid contact events of saithe would not lead to a length-dependent chance of passing through the grid. Haddock had the highest grid contact frequency compared to the other three species. On average, cod had to make at least three attempts to escape through the grid, while haddock, saithe and redfish needed approximately two attempts to escape. Squeezing was a significant factor in escape for all four species, as 42% of cod, 6% of haddock, 53% of saithe and 17% of redfish were estimated to do so. The quantified behaviours explain why the size selectivity of fish-sorting grids has been found to be sub-optimal.

Effect of gillnet mesh size on catch efficiency and bycatch in the Greenlandic lumpfish (Cyclopterus lumpus) fishery - Malthe Kjølhede Ahlmann Olesen; Bent Herrmann; Rikke Petri Frandsen; Flemming R. Merkel; Cas Van Der Kaaden; Søren Post (Estuarine, Coastal and Shelf Science, 2025)

Letter to the Editor re: Millar and Broadhurst (2025): “Incorrect inference from size-selectivity studies due to widespread misuse of bootstrap confidence bands” [Fisheries Research 281, 107225] - Bent Herrmann; Juan Santos; Manu Sistiaga; Jure Brčić; Junita D. Karlsen; Valentina Melli; Antonello Sala; Tiago Veiga-Malta; Jesse Brinkhof; Andrea Petetta; Mengjie Yu; Mark J.M. Lomeli; et al. (Fisheries Research, 2025)

Assessing trawls size selectivity in Antarctic krill: The role of sex and maturity stages - Ludvig Ahm Krag; Jure Brčić; Bent Herrmann; Marco Nalon; Bjørn Arne Krafft (Regional Studies in Marine Science, 2025)

Performance of an excluder grid to mitigate bycatch of sharks in deep-water red shrimp trawl fishery - Yunus Emre Fakıoğlu; Gökhan Gökçe; Bent Herrmann; Hüseyin Özbilgin (Journal for Nature Conservation, 2025)

Increase in catch efficiency using a semicircular ground gear in demersal trawls - Manu Sistiaga; Jesse Brinkhof; Ilmar Brinkhof; Bent Herrmann; Hermann Pettersen (Reviews in Fish Biology and Fisheries, 2025)
In demersal trawls, ground gears are typically fixed to the fishing line to protect against the seabed and ensure seabed contact. Rockhoppers (RH) are among the most applied types of ground gears, especially in fisheries with rough seabed. However, their use has earlier been associated with substantial loss of catch under the fishing line and low catch efficiency. A new ground gear concept known as the semicircular spreading gear (SCSG) has been documented to reduce this loss, but the catch efficiency of RH and SCSG gears has never been directly compared in a systematic commercial scale trial. Using twin trawl configuration, the present study compared the catch efficiency of a RH gear and a SCSG gear with both size selective and blinded trawls. Eighteen hauls were conducted in the Barents Sea demersal trawl fishery where cod ( Gadus morhua ) and haddock ( Melanogrammus aeglefinus ) are target species and redfish ( Sebastes spp.) is an important commercial bycatch species. Using size selective trawls, the catches with the trawl equipped with the SCSG resulted in an average increase of 25.44 for cod, 32.04 for haddock and 64.34% for redfish compared to the trawl equipped with the RH gear. With blinded trawls, the increase changed to 41.35, 65.76 and 44.23% for cod, haddock and redfish, respectively. Despite the significant increase in catch efficiency observed for the trawl equipped with the SCSG, it also caught significantly more undersized fish than the trawl equipped with the RH gear. This increase illustrates the importance of size selective devices, especially if the use of the SCSG is widely adopted by industry.

Understanding and predicting codend size selection for flatfish species - Zita Bak-Georgsen; Bent Herrmann; Valentina Melli; Juan Santos; Jordan P. Feekings (Reviews in Fish Biology and Fisheries, 2025)
In several demersal trawl fisheries flatfish constitute a large part of the catch, but often a significant fraction of these flatfish are unwanted species or sizes. To design trawls that are capable of addressing this problem, it is necessary to understand and quantify the size selection of flatfish species in trawls. Therefore, based on laboratory experiments, we tested the ability of different sizes of three flatfish species, plaice ( Pleuronectes platessa ), flounder ( Platichthys flesus ) and dab ( Limanda limanda) to physically pass through diamond meshes of different sizes and opening angles. By combining these results with results from fishing trials, we were able to determine that the angle at which fish contact the meshes during an escape attempt plays a major role in the size selection of flatfish species. Contrarily, wiggling movement and the ability to squeeze through the mesh during escape attempts have a very limited effect. On the basis of these insights, we produced guidelines for the sizes and shapes of meshes in trawl codends to match the desired harvesting pattern of the three flatfish species investigated.

Understanding and predicting size selectivity of saithe (Pollachius virens) in trawl codends - Jesse Brinkhof; Manu Sistiaga; Bent Herrmann; Zita Bak-Jensen; Nadine Jacques (Reviews in Fish Biology and Fisheries, 2025)
Saithe ( Pollachius virens ) is common in the Northern Atlantic and is often captured with demersal and pelagic trawls that comprise diamond mesh codends. However, size selectivity data is scarce for saithe. The meshes in these trawl codends have limited openness due to the drag forces acting on the catch accumulation in the aft end, which reduces escape opportunities for roundfish like saithe. Shortening lastridge ropes attached to codend selvedges can increase codend mesh openness and make it more constant though the capture process potentially improving size selectivity. Thus, this study investigated the size selectivity of saithe in diamond mesh codends with two different configurations: lastridges with the same length as the codend selvedges and 15% shortened lastridge ropes. Results from experimental fishing proved that shortened lastridge ropes increased codend size selection of saithe. By combining these results with saithe morphology data relevant for mesh size selectivity, we were able to gain deeper understanding on codend size selectivity for this species and the influence of the shortened lastridge ropes. The analysis conducted enabled us to predict the size selectivity of saithe for codends with a mesh size different to that tested in the sea trials. By comparing our predictions for codend size selection with results obtained based on experimental fishing reported in literature, we demonstrate that our predictions are well-aligned with experimental results obtained for a wide range of codend mesh sizes. Our approach and results can act as guidelines for technical regulations and codend design in saithe fisheries leading to exploitation patterns that comply with local legislations as the minimum legal size defined by the authorities.

Size matters for the efficiency of sorting grids in demersal trawls - Manu Sistiaga; Bent Herrmann; Jesse Brinkhof; Hermann Pettersen; Dagfinn Lilleng; Liz Kvalvik; Jostein Saltskår; Kristian L. Skaar (Fisheries Research, 2025)

Estimating size selectivity of Calanus spp. in plankton trawls: effect of mesh size for commercial fishery - Enis N. Kostak; Bent Herrmann; Eduardo Grimaldo; Jesse Brinkhof (Reviews in Fish Biology and Fisheries, 2025)
Calanus spp. are marine zooplankton that are considered as a potential source for aquaculture feed, due to their high abundance in the North Atlantic. The diminutive size (< 5 mm) of these zooplankton necessitates the use of fine-meshed trawls to harvest them efficiently. However, the use of fine-meshed trawls leads to high drag and thus energy demand to tow the trawl. Therefore, it is of importance to know the effect of mesh size on the capture efficiency of Calanus, and specifically to quantify which sizes of those that can be harvested effectively depending on mesh size in the trawl. Therefore, experimental trawl fishing targeting Calanus was conducted testing gears differing in mesh size to estimate their size selectivity. We used an image and artificial intelligence-based specially built and trained acquisition method to rapidly measure the size of large numbers of Calanus to prepare the catch data for size selectivity analysis . The results demonstrate a clear size selection process of Calanus in nets with mesh sizes considered for this fishery . Specifically, the size selectivity would result in a loss of 10%, 45% and 99% of Calanus if the trawl has a mesh size of 500, 750 and 1000 μm, respectively.

Size selection in sampling nets leads to underestimation of microplastic pollution - Mengjie Yu; Bent Herrmann; Hui Liang; Manu Sistiaga; Zecong Zhu; Jure Brčić; Lulu Tang; Changdong Liu; Yanli Tang (Environmental Pollution, 2025)

Using species-specific behavior to improve catch efficiency of target species in mixed trawl fisheries - Ludvig A. Krag; Rikke P. Frandsen; Bent Herrmann; Grete E. Dinesen; Junita D. Karlsen (Fisheries Research, 2025)

Size selectivity of Muller’s pearlside (Maurolicus muelleri), glacier lanternfish (Benthosema glaciale) and krill in trawls targeting the mesopelagic fish - Enis N. Kostak; Bent Herrmann; Eduardo Grimaldo; Jesse Brinkhof (Fisheries Research, 2025)

Can automatic measuring replace humans when evaluating a shrimp fishery? - Bent Herrmann; Elling Ruud Øye; Jonatan Sjølund Dyrstad; Anja Helene Alvestad (Regional Studies in Marine Science, 2024)

Ghost fishing by self-baited lost, abandoned or discarded pots in snow crab (Chionoecetes opilio) fishery - Kristine Cerbule; Bent Herrmann; Roger B. Larsen; Mengjie Yu (Journal for Nature Conservation, 2024)

Observing fish behavior in towed fishing gear—is there an influence of artificial light? - Jesse Brinkhof; Manu Sistiaga; Bent Herrmann; Junita D. Karlsen; Eduardo Grimaldo; Nadine Jacques; Zita Bak-Jensen (Reviews in Fish Biology and Fisheries, 2024)
Fish behavior is important to consider when developing selective fishing gear. In studies designed to investigate the size selective properties of towed fishing gears such as trawls, fish behavior is mainly documented by underwater video recordings. Because fishing gear can be operated at great depths or in other low light environments, artificial light is often required for underwater recordings. However, artificial light can influence fish behavior, which casts doubt on the validity of behavioral observations obtained in the presence of artificial light. However, removing artificial light disables video recordings and the possibility to study fish behavior in relation to selectivity devices towed fishing gears in low light environments. To date, little is known about the extent to which artificial light used for video observations affects fish behavior with respect to fishing gear. Therefore, we conducted fishing trials in the Barents Sea demersal trawl fishery to assess the effect of light sources on fish behavior by using size selectivity results in towed fishing gears. We found that the behavior of cod ( Gadus morhua ) was unaffected by the light sources, whereas the behavior of haddock ( Melanogrammus aeglefinus ), saithe ( Pollachius virens ) and redfish ( Sebastes spp.) significantly changed when red light and white light were employed. Our results also demonstrated significant differences in fish behavior between white and red light.

Semi-pelagic trawling in the U.S. West Coast groundfish bottom trawl fishery: Effects on catch efficiency and seafloor interactions - Meagan Abele; Mark J.M. Lomeli; W. Waldo Wakefield; Bent Herrmann (Ocean & Coastal Management, 2024)

Trade-off between drag and catch performance when designing zooplankton trawls - Enis N. Kostak; Eduardo Grimaldo; Jesse Brinkhof; Bent Herrmann (Ocean Engineering, 2024)

Use of floated gillnet to reduce flatfish bycatch in a mixed-species gillnet fishery - Mengjie Yu; Bent Herrmann; Kristine Cerbule; Changdong Liu; Liyou Zhang; Yanli Tang (Estuarine, Coastal and Shelf Science, 2024)

The effect of soak time on pot escape opening selectivity in swimming crab (Portunus trituberculatus) fishery - Mengjie Yu; Bent Herrmann; Kristine Cerbule; Changdong Liu; Yilin Dou; Liyou Zhang; Linjie Li; Yanli Tang (Fisheries Research, 2024)

Efficient and sustainable: innovative pot design for a Mediterranean small-scale fishery - Massimo Virgili; Andrea Petetta; Bent Herrmann; Kristine Cerbule; Stefano Guicciardi; Daniel Li Veli; Giulio Barone; Alessandro Lucchetti (Frontiers in Marine Science, 2024)
Pots are traditional fishing gear type largely employed in Mediterranean Small Scale Fisheries (SSFs). Their often higher species selectivity and catch quality compared to other gear types such as passive set nets or trawls are appealing characteristics for reducing the impact on benthic communities and diversifying fishing effort in the region. Despite this, in some SSFs, pots are still rarely used as prevalent gear due to low landings and profits. The present study investigated if an experimental pot design of two different colours could improve the catch efficiency for mantis shrimp ( Squilla mantis ) in the Adriatic coastal SSF, compared to the traditionally used design. The experimental design in white colour increased the catch efficiency for S. mantis compared to the same design in black colour and the traditional pots, while the catch efficiency for black goby ( Gobius niger , another commercial species) was higher in the experimental design regardless of the colour. Furthermore, the species composition in catches was not significantly affected with the use of the experimental design, neither in target nor in bycatch species, therefore not causing negative effect on the species community. Finally, the experimental pot design also led to some improvements in gear durability, ensuring a higher resistance to wear, sea currents and marine fouling. The promising results obtained with this new design could broaden the interest towards increased use of pots as alternative and low impact gear in other Mediterranean areas.

Are rigid sorting devices necessary to control size selectivity in demersal trawl fisheries? - Bent Herrmann; Zita Bak-Jensen; Manu Sistiaga; Jesse Brinkhof; Roger B. Larsen; Eduardo Grimaldo; Kristine Cerbule; Enis N. Kostak; Morteza Eighani (Regional Studies in Marine Science, 2024)

Selectivity in snow crab (Chionoecetes opilio) pot fishery: Effect of escape gap shape and size for conservation of fishery resources - Kristine Cerbule; Bent Herrmann; Jure Brčić; Eduardo Grimaldo; Zita Bak-Jensen (Journal for Nature Conservation, 2024)

Ghost fishing efficiency in swimming crab (Portunus trituberculatus) pot fishery - Mengjie Yu; Bent Herrmann; Kristine Cerbule; Changdong Liu; Yilin Dou; Liyou Zhang; Yanli Tang (Marine Pollution Bulletin, 2024)

Effect of mesh size in monofilament and multifilament gillnets on catch efficiency in the Black Sea whiting (Merlangius merlangus) fishery - Cemil Altuntaş; Adnan Tokaç; Bent Herrmann; Devrim Selim Mısır; Murat Dağtekin; Kristine Cerbule (Estuarine, Coastal and Shelf Science, 2024)

One mesh does not fit all: A dual compartment codend provides flexible selectivity opportunities to manage mixed fisheries - Junita D. Karlsen; Ludvig Ahm Krag; Bent Herrmann (Ocean & Coastal Management, 2024)

Effect of artificial lights on catch efficiency and capture patterns in Asian paddle crab (Charybdis japonica) gillnet fishery - Mengjie Yu; Bent Herrmann; Kristine Cerbule; Changdong Liu; Liyou Zhang; Yanli Tang (Regional Studies in Marine Science, 2023)

Understanding the effect of design parameters on the filtration efficiency of trawls intended for commercial harvesting of zooplankton - Eduardo Grimaldo; Bent Herrmann; Enis N. Kostak; Jesse Brinkhof (Ocean Engineering, 2023)

Comparison of physical properties and fishing performance between biodegradable PLA and conventional PA trammel nets in grey mullet (Mugil cephalus) and red-lip mullet (Liza haematocheila) fishery - Mengjie Yu; Yanli Tang; Minghua Min; Bent Herrmann; Kristine Cerbule; Changdong Liu; Yilin Dou; Liyou Zhang (Marine Pollution Bulletin, 2023)

Effect of grid section design on trawl size selectivity - Manu Sistiaga; Bent Herrmann; Jesse Brinkhof; Roger B. Larsen (Regional Studies in Marine Science, 2023)

Ghost fishing efficiency by lost, abandoned or discarded pots in snow crab (Chionoecetes opilio) fishery - Kristine Cerbule; Bent Herrmann; Eduardo Grimaldo; Jesse Brinkhof; Manu Sistiaga; Roger B. Larsen; Zita Bak-Jensen (Marine Pollution Bulletin, 2023)

The capability of square-meshes and fixed-shape meshes to control codend size selection - Zita Bak-Jensen; Bent Herrmann; Juan Santos; Valentina Melli; Daniel Stepputtis; Jordan P. Feekings (Fisheries Research, 2023)

Use of biodegradable materials to reduce marine plastic pollution in small scale coastal longline fisheries - Kristine Cerbule; Bent Herrmann; Željka Trumbić; Mirela Petrić; Svjetlana Krstulović Šifner; Eduardo Grimaldo; Roger B. Larsen; Jure Brčić (Journal for Nature Conservation, 2023)

Simple pot modification improves catch efficiency and species composition in a tropical estuary mud crab (Scylla serrata) fishery - V.R. Madhu; Sreelakshmi B. Anand; Kristine Cerbule; Bent Herrmann (Estuarine, Coastal and Shelf Science, 2023)

Effects of Codend Mesh-Shape and Size on the Size Selectivity of Demersal Trawl Targeting Banded Scad (Alepes djedaba) in the Beibu Gulf, South China Sea - Bingzhong Yang; Bent Herrmann; Rong Wan (Journal of Marine Science and Engineering, 2023)
In order to optimize the size selectivity of demersal trawl targeting Banded Scad, Alepes djedaba, in the South China Sea (SCS), we tested and compared the selective properties of four experimental codends. These codends included two diamond-mesh codends (T0 codends) with different mesh openings (30 and 35 mm), and two T90 codends (the netting was turned by 90 degrees) with the relatively same mesh opening. The results demonstrated that the T0_30 codend (diamond-mesh codend with 30-mm mesh opening) presented the best size selectivity and is a potential choice to harvest Banded Scad in the studied area among the codends tested. Although applying the T0_35 or T90_30 codend might obtain a little improvement in size selectivity, the loss of marketable-size individuals could be a compromise. Considering the results in our study and those of previous studies, we recommend that the T0_30 codend should be mandated in the fisheries management regulation of trawl fisheries targeting Banded Scad in the SCS.

Testing of hook sizes and appendages to reduce yelloweye rockfish bycatch in a Pacific halibut longline fishery - Mark J.M. Lomeli; W. Waldo Wakefield; Meagan Abele; Claude L. Dykstra; Bent Herrmann; Ian J. Stewart; Gregory C. Christie (Ocean & Coastal Management, 2023)

Effect of gillnet twine thickness on capture pattern and efficiency in the Northeast-Arctic cod (Gadus morhua) fishery - Ilmar Brinkhof; Bent Herrmann; Roger B. Larsen; Jesse Brinkhof; Eduardo Grimaldo; Jørgen Vollstad (Marine Pollution Bulletin, 2023)

Is there a limit to the potential effects of shortening lastridge ropes on the size selectivity of diamond mesh codends? - Manu Sistiaga; Bent Herrmann; Jesse Brinkhof; Roger B. Larsen; Juan Santos; Daniel Stepputtis; Ilmar Brinkhof; Nadine Jacques; Kristine Cerbule; Andrea Petetta; Elsa Cuende; Liz Kvalvik (Fisheries Research, 2023)

Improved bycatch reduction in the mixed demersal trawl fishery for Norway pout (Trisopterus esmarkii) - Eduardo Grimaldo; Jesse Brinkhof; Bent Herrmann; Kristine Cerbule; Leif Grimsmo; Hermann Pettersen (Estuarine, Coastal and Shelf Science, 2023)

Impacts on biodiversity from codend and fisher selection in bottom trawl fishing - Chryssi Mytilineou; Bent Herrmann; Christopher J. Smith; Danai Mantopoulou-Palouka; Aikaterini Anastasopoulou; Apostolos Siapatis; Antonello Sala; Persefoni Megalofonou; Nadia Papadopoulou; Vassiliki Vassilopoulou; Caterina Stamouli; Stefanos Kavadas; et al. (Frontiers in Marine Science, 2022)
Fisheries have important impacts on marine biodiversity. In this work, combined information on the abundance, species richness, diversity indices, species composition, trophic level and vulnerability index were examined for the first-time to detect differences in five units related to trawl fishing: the fish assemblage entering the trawl codend, and the escaping, retained, discarded and landed fractions, derived by the gear and fisher selection practices. The work was based on a case study conducted in the Mediterranean Sea, using three different meshes in the trawl codend (40mm-40D and 50mm-50D diamond meshes, and 40 mm-40S square meshes) and a cover of the codends with small mesh size. In general, trawl fishing produces an escaping fraction that was always lower in abundance, richness, and vulnerability index, similar in diversity indices and trophic level, and different in species composition compared to the fish assemblage entering the codend. In almost all cases, fishers selected as landings a fraction that was the lowest in diversity indices, and the highest in trophic level. In contrast, fishers discarded a fraction that was the highest in diversity and vulnerability index, and the lowest in trophic level. Although the three codends did not differ significantly in the fraction of escapees in terms of diversity indices, trophic level, and vulnerability index, the 40S codend showed a significantly higher percentage in the escaping number of species and individuals, and less differences in the species composition; in addition, lower percentage in abundance of discards and higher of landings in the retained catch (0.6:1) than did the other two codends (0.9:1). It was suggested that an urgent modification of the trawl for the elimination of the discarded highly vulnerable species (e.g. Elasmobranchs) is needed, and that trawl species-selectivity should be improved by allowing escape or avoiding catch of the discarded fraction to minimize biodiversity losses.

Escape of hake (Merluccius merluccius), horse mackerel (Trachurus trachurus) and blue whiting (Micromesistius poutassou) in codends with shortened lastridge ropes - ELSA CUENDE; MANU SISTIAGA; BENT HERRMANN; MIKEL BASTERRETXEA; LUIS ARREGI (Mediterranean Marine Science, 2022)
Diamond meshes in trawl codends have limited openness, which reduces escape opportunities for roundfish. Shortening the lastridge ropes (LR) attached to codend selvedges can increase the availability of open meshes resulting in higher chances of escape. However, this availability does not imply optimal mesh openness, nor does it guarantee use. We estimate the escape probability of hake, horse mackerel and blue whiting through a 20% shortened LR codend and a standard codend, and quantify the contribution of different mesh opening angles (OAs) to their size selectivity. The results confirm that high OAs increase escape opportunities for all species. However, shortened LR only improved size selectivity significantly for horse mackerel and blue whiting. This difference between species may be related to behavioural differences. The mesh openness achieved with 20% shortened LR was below that necessary to obtain optimal escape opportunities for these species. The study highlights the relevance of considering fish morphology and behaviour to optimally exploit size selectivity when designing shortened LR codends.

Simple and effective: T90 codends improve size selectivity and catch efficiency compared with diamond-mesh codends for mantis shrimp (Oratosquilla oratoria) in demersal trawl fishery of the South China Sea - Bingzhong Yang; Bent Herrmann (Frontiers in Marine Science, 2022)
Size selectivity and catch efficiency of four codends were tested and compared for mantis shrimp ( Oratosquilla oratoria ) in demersal trawl fisheries of the South China Sea (SCS). These codends were differing in mesh shapes, diamond mesh (T0) and diamond-mesh turned 90° (T90) with mesh sizes of 30 and 35 mm, respectively. The results demonstrated that the T0 codend with a lower mesh size, 30 mm, presented poorer selective properties for the target species, while size selectivity would be significantly improved with the mesh size increasing to 35 mm, or substituting the T0 codend with the T90 codend. For the T90 codend with a larger mesh size, 35 mm, the size selectivity was the highest, whereas the loss of the legal individuals was also significantly considerable. Considering the trade-off between releasing undersized individuals and maintaining the legal ones, the T0 codend with 35-mm mesh size or the T90 codend with 30-mm mesh size might be a better choice to target mantis shrimp in demersal trawl fisheries of the SCS.

Effect of codend mesh sizes on the size selectivity and exploitation pattern of cocktail shrimp (Trachypenaeus curvirostris) in shrimp trawl fishery of the South China Sea - Bingzhong Yang; Bent Herrmann (Frontiers in Marine Science, 2022)
This study aims at improving fishery management by testing and comparing the size selectivity and exploitation pattern of diamond-mesh codends, with mesh sizes ranging from 25 to 54 mm, for cocktail shrimp ( Trachypenaeus curvirostris ) in the South China Sea (SCS). Beginning from 25 mm, the minimum mesh size regulated by the shrimp trawl fishery industry, we investigated how the mesh sizes of the codends would affect the size selectivity and exploitation pattern in reference to the minimum conservation reference size (MCRS, 7.0 cm total length) of cocktail shrimp in the SCS. According to our results, the selective properties of the codend mesh sized at 25 mm in line with the regulation failed to protect the undersized individuals of cocktail shrimp because of its 50% retention length of 5.85 cm (confidence interval, CI: 5.16–6.18 cm), far less than the MCRS of cocktail shrimp. As the retention probability of a shrimp with a MCRS length was as high as 97.45 % (CI: 86.86–100.00%), more than 40% of the undersized shrimp was retained. It was proved that increasing the codend mesh size did not significantly improve the size selectivity and exploitation pattern which might be improved by other gear modifications.

Effect of Extension Piece Design on Catch Patterns in a Mediterranean Bottom Trawl Fishery - Andrea Petetta; Bent Herrmann; Massimo Virgili; Daniel Li Veli; Jesse Brinkhof; Alessandro Lucchetti (Frontiers in Marine Science, 2022)
The catch composition of bottom trawls is commonly refined and improved through changes in codend design. Measures like reducing the number of meshes in codend circumference or turning diamond netting by 90 degrees are well known to improve the size selectivity of fish species with rounded cross-sectional shape. Based on this we speculated whether the same measures, if applied in other parts of a bottom trawl, would provide similar benefits as in the codend. Therefore, experiments were carried out by deploying these changes to the trawl extension piece in a Mediterranean bottom trawl fishery. However, for European hake and monkfish, results showed no indication of improved selectivity or catch pattern compared to the standard extension piece in the trawl. Contrary, for red mullet, one of the most important species in this fishery, reducing the number of meshes in the circumference of the extension piece jeopardized the size selection obtained in the trawl with a standard extension piece. The lesson learnt from this study was that the design changes that work for the codend do not necessarily work for other parts of the trawl. In fact, they can even have negative effects.

Catch Pattern for Antarctic krill (Euphausia superba) of Different Commercial Trawls in Similar Times and Overlapping Fishing Grounds - Zhongqiu Wang; Hao Tang; Bent Herrmann; Liuxiong Xu (Frontiers in Marine Science, 2021)
Antarctic krill ( Euphausia superba ) is harvested using different design midwater trawls. Knowing the selective properties between trawls is crucial information for the management of the krill resources. This study compared the catch patterns between different commercial krill trawls at similar times and overlapping fishing grounds based on scientific data collected by scientific observers onboard commercial trawlers Long Teng (LT) and Fu Rong Hai (FRH). The results showed significant differences in the length-dependent catch densities and cumulative catch densities of krill between the two trawls. The krill length range in catches from LT's trawl was wider than that of FRH's trawl. Furthermore, the catch would consist of a larger proportion of smaller krill in the LT's trawl. The LT's trawl caught significantly higher proportions of krill below 38 mm than FRH's trawl. Even, the LT's trawl caught substantial numbers of krill <30 mm, whereas the FRH's trawl caught very few of them. The main factors causing the difference between trawls in catch pattern were inferred to be related to gear design including differences in mesh sizes used. The results of this study enhance the quality of comparative analysis of scientific data from commercial trawls and the understanding of gear selectivity of different configuration trawls used for harvesting krill.

Estimating selectivity of experimental diamond (T0) and turned mesh (T90) codends in multi-species Mediterranean bottom trawl - ANDREA PETETTA; BENT HERRMANN; MASSIMO VIRGILI; ROCCO De MARCO; GIOVANNI CANDUCI; DANIEL Li VELI; GIADA BARGIONE; CLAUDIO VASAPOLLO; ALESSANDRO LUCCHETTI (Mediterranean Marine Science, 2020)
The effect of shifting from a diamond mesh codend (T0) to a 90° turned mesh codend (T90) on the size selectivity of seven commercially important species in the Mediterranean bottom trawl fishery was evaluated. During sea trials conducted in the north-western Adriatic, two experimental codends made of 54 mm nominal mesh size netting that differed only in mesh configuration were alternately mounted on the same trawl. Overall, the size selectivity was significantly improved for all the species analysed, shifting from T0 to T90. The difference in the average expected L50values between T90 and T0 was particularly marked in European hake (Merluccius merluccius, 21.26 vs 11.26 cm total length), common squid (Loligo vulgaris, 12.06 vs 7.88 cm mantle length) and mantis shrimp (Squilla mantis, 20.78 vs 13.35 mm carapace length). Both codends had an excessive size selectivity especially for red mullet (Mullus barbatus), Mediterranean horse mackerel (Trachurus mediterraneus) and whiting (Merlangius merlangus), thus involving a commercial loss. These findings demonstrate the efficiency of the T90 codend tested at excluding undersized specimens, especially of hake, whose average L50was above the minimum conservation reference size of 20 cm. The adoption of this practical and inexpensive solution could help improve the management of the demersal resources targeted by the Mediterranean bottom trawl fishery.

Effect of a lateral square-mesh panel on the catch pattern and catch efficiency in a Mediterranean bottom trawl fishery - SARA BONANOMI; JURE BRČIĆ; BENT HERRMANN; EMILIO NOTTI; ALESSANDRO COLOMBELLI; FABRIZIO MORO; JACOPO PULCINELLA; ANTONELLO SALA (Mediterranean Marine Science, 2020)
The current legal codends used in Mediterranean bottom trawl fisheries are at high risk of retaining undersized individuals of several commercial fish species. This entails that codends alone are unable to provide the desired exploitation pattern. A simple technological measure that potentially can provide higher release efficiency of undersized fish are Square-Mesh Panels (SMPs). SMPs are often applied in the upper section of the trawl belly, just ahead the codend. However, recent studies in the Mediterranean have demonstrated that SMPs mounted in this position provided limited release efficiency, because very few fish came into contact with their meshes. In attempt to improve SMPs efficiency in the Mediterranean bottom trawl fisheries, we applied them on the lateral sides of the last tapered section of the trawl belly, just ahead of the codend, and fitted two guiding panels in the trawl belly to enhance fish-SMP contact. We compared the catch performance of a standard commercial trawl with a 52 mm diamond-mesh codend and of a similar trawl fitted with lateral SMPs (70 mm mesh size) in the belly using a twin trawl. The study focused on red mullet (Mullus barbatus), a commercially important species, but data for gurnard (Chelidonichthys lucerna and Chelidonichthys cuculus) were also obtained and analysed. In contrast to previous research on SMPs mounted in the top panel of the trawl, in this study SMPs induced a significant effect on catch performance for red mullet, demonstrating that their lateral position involved greater fish-SMP contact. However, since the test trawl lost a significant amount of legal-sized red mullet compared with the standard trawl, the effect was not wholly positive, possibly due to an excessively large mesh size. Therefore, future studies should be encouraged to test lateral SMPs with smaller mesh sizes.

Combining selection models and population structures to inform fisheries management: a case study on hake in the Mediterranean bottom trawl fishery - CHRYSSI MYTILINEOU; BENT HERRMANN; STEFANOS KAVADAS; CHRIS J. SMITH; PERSEFONI MEGALOFONOU (Mediterranean Marine Science, 2020)
The reduction of juvenile catch and discards are important targets in fisheries policy. This work examines how selection models can predict the size structure (LFD) of discards and landings considering the effects of area, time period, gear and fisher behaviour. Additional exploitation indicators related to the gear used, fisher's selection pattern, and discards were also estimated. The approach is demonstrated in a study concerning hake in the Mediterranean trawl fishery, focusing on high (HRA) and low (LRA) recruitment areas in the Saronikos Gulf (Eastern Mediterranean) during two periods (June, September) using two codends (40 mm square-40S, 50 mm diamond-50D mesh). The predicted discards LFDs revealed generally higher percentages in the HRA in June when using the 50D. The predicted landings LFDs showed higher percentages in the LRA in September for both codends, but undersized hake were always included. LFDs and exploitation indicators indicated that both codends were inappropriate for sustainable fishing of hake in the HRA, where 50D performed worse than the 40S. Fishing with both codends in the LRA in September revealed the lowest discards rates and minimum sizes of landings close to MCRS (minimum conservation reference size). These results can provide information to fisheries management aiming to protect juveniles and reduce discards through spatio-temporal fishing closures.

Predicting optimal combinations of by‐catch reduction devices in trawl gears: A meta‐analytical approach - Valentina Melli; Bent Herrmann; Junita Diana Karlsen; Jordan Paul Feekings; Ludvig Ahm Krag (Fish and Fisheries, 2020)
Global efforts to reduce unwanted catches have led to the development of a vast array of by‐catch reduction devices (BRDs), in particular for mixed trawl fisheries. Some of these BRDs could likely benefit from being combined. However, the number of possible combinations would be prohibitive to be tested experimentally. Therefore, in this study we propose a meta‐analytical approach that combines the data available on BRDs tested independently in a fishery and predict the theoretical selectivity of all possible combinations of those devices. This allows to identify promising BRD combinations, worth experimental investigation and flexible trawl configurations, where the selectivity can be substantially modified by adding or removing one BRD, thus aiding fishermen in adapting to high variability in catch composition and quota availability. To illustrate the approach, we used BRDs developed for the well‐studied Nephrops ( Nephrops norvegicus, Nephropidae) directed mixed trawl fishery in the Skagerrak and Kattegat seas. We predicted the selectivity of 100 BRD combinations for Nephrops , cod ( Gadus morhua, Gadidae) and haddock ( Melanogrammus aeglefinus, Gadidae), compared them in terms of absolute selectivity and performance under realistic catch scenarios, from both single‐ and multispecies perspectives, and identified 15 BRD combinations that could be worth future experimental investigation. The meta‐analytical approach makes best use of existing knowledge and leads to new insights about the potential for improvement and flexibility in trawl selectivity. This could benefit a variety of mixed trawl fisheries and help developing a new generation of more flexible gears, with multiple BRDs integrated in their structure.

Mesh sticking probability in fishing gear selectivity: Methodology and case study on Norway lobster (Nephrops norvegicus) and mantis shrimp (Squilla mantis) in the Mediterranean Sea creel fishery - JURE BRČIĆ; BENT HERRMANN; MARINA MAŠANOVIĆ; SVJETLANA KRSTULOVIĆ ŠIFNER; MATEJA BARANOVIĆ; FRANE ŠKELJO (Mediterranean Marine Science, 2019)
Fish or crustaceans stuck in the fishing gear meshes can lead to operational problems in some fisheries and thereby affect theeconomic gain. However, mesh sticking probability has never been formally quantified as a part of the estimation of fishing gearsize selectivity. Therefore, this study developed a size selection model and estimation procedure that, besides the size dependentretention and escape probabilities, includes the size dependent mesh sticking probability. The new method was applied to quantify the size dependent retention, sticking and escape probabilities for mantis shrimp (Squilla mantis) and Norway lobster (Nephrops norvegicus) in creels with 41 mm square mesh netting. The mesh sticking probability was found to display a bell-shaped curvature with a maximum value for a specific carapace length and decreasing probabilities for both smaller and bigger individuals. For mantis shrimp the maximum sticking probability was found for 32.5 mm carapace length with a value at 13.5%, while 63.1% and 23.4% of that size were respectively retained inside the creels and escaped. For Norway lobster the maximum sticking probabilitywas 2% and occurred for 34.0 mm carapace length. The method and estimation procedure presented in this study might be applicable for quantifying mesh sticking probability as an integral part of future fishing gear size selectivity studies on other speciesand fisheries.

The efficiency of sieve‐panels for bycatch separation in Nephrops trawls - Juan Santos; Bent Herrmann; Bernd Mieske; Ludvig A. Krag; Stefanie Haase; Daniel Stepputtis (Fisheries Management and Ecology, 2018)
This study investigated the efficiency of a sieve‐panel concept, intended to separate bycatch species from Nephrops (Norway lobster) in a trawl gear via mechanical and behavioural means. Four different designs of varying panel mesh size or inclination were tested in experimental fishing. For each design, the length‐dependent sieving efficiency, defined as the fraction of Nephrops or fish passing through the panel to the lower codend, was estimated. The sieving efficiency for Nephrops increased from ~17% to ~71% as mesh size increased, and decreased with increasing carapace length, but did so less as panel inclination and mesh size increased. The sieving efficiency for roundfish was low, as intended, while the efficiency for flatfish decreased with fish size. Although results are promising, the sieving efficiency for the largest, most valuable Nephrops remained too low. Therefore, further improvements are necessary before the concept is acceptable to the commercial fishing fleet.